Investigation of the reaction times of 13-14 years old video game players and racket athletes - Zühtü Birinci, Y.; Sahin, S.; Pancar, S. (European Journal of Physical Education and Sport Science, 2018)
The aim of the presented research was to examine the reaction times of 13-14-years old racket athletes (RAs) (badminton, table tennis, court tennis) and video game players (VGPs). A total of 96 subjects (68 male, 28 female) participated voluntarily in the research. The mean age of the participants was 13.38± 0.74 years, body weight was 50.60 ±1.5 kilograms (kg), stature was 157.42 ± 13.12 centimeters (cm). The individuals who met the criterion of spending at least 10 hours a week by training / playing video games for at least 5 years were called as RAs / VGPs. RT against auditory and visual stimuli were recorded by using a MP36 device (Biopac System, USA). Shapiro-Wilk test was used to evaluate whether continuous variables were normally distributed. Mann-Whitney U-test and Independent Samples "t" test were used for the comparisons of continuous variables between the groups. Pearson and Spearman rank correlation coefficients were used to evaluate the correlations between the continuous variables. Statistical significance level was accepted as p<0.05. SPSS v.21 program was used for statistical analyzes. A statistically significant difference was determined in terms of audio-visual right hand RT (p<0.001) and audio-visual left hand RT (p<0.01) when compared values of VGPs to those of sedentary. However, no statistically significant difference was detected in the audio-visual right-left hand RT values of the VGPs compared to the RAs (p> 0.05). In conclusion, it was determined that the audio-visual hand RT values were similar for the VGPs and RAs.